English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

7 answers

13 + 13 - 6/3 = 24
6 * (13/13 + 3) = 24
(3+13/13)! = 24
(6 - 3 + 13/13)! = 24
(13 - 6 - 3)! = 24

you didnt say use them all.
these are all different.

2006-12-04 19:54:36 · answer #1 · answered by oscarD 3 · 3 0

(13+13) - (6/3) = 24
6 * (3 + 13/13) = 24
13 - (6/3) + 13 = 24
(3 + 13/13) * 6 = 24
(-6/3) + 13 + 13 = 24

Edit: The last three equations are really just rearrangements of the first two equations.

If you can use factorial (!) then you have some more possibilities:
(3 + (13 - 13)!) * 6 = 24
6 * (3 + (13/13)!) = 24
(6 - 3 + (13/13))! = 24
((6 * (13 - 13))! + 3)! = 24

I like the last one because it uses all the four numbers but still manages to make 4! in a creative way.

2006-12-04 19:12:18 · answer #2 · answered by Puzzling 7 · 2 1

Here are 5 different ways using ALL the numbers:

1) (3 + 13/13)*6
2) 13 + 13 - 6/3
3) (3 + (13 - 13)!)*6
4) (6 - 3 + 13/13)!
5) [3 + {arcos(13/13)}!]*6

2006-12-04 21:03:07 · answer #3 · answered by Wal C 6 · 1 1

In Puzzling's answers, #1, #3, and #5 are the same; #2 and #4 are the same . So that is only TWO different equations.

VOTE FOR "OSCAR S"

2006-12-04 19:34:38 · answer #4 · answered by Overrated 5 · 2 0

13 + 13 - 6 / 3

there's an obvious one

2006-12-04 19:13:04 · answer #5 · answered by Anonymous · 0 0

Puzzling got 'em all. Good job. Fun question.

2006-12-04 19:26:14 · answer #6 · answered by Gwen K 2 · 0 1

(13+13)-(6/3)=24
-(6/3)+(13+13)=24
-6/3+13+13=24
13+(-6/3)+13=24
6/-3+13+13=24

2006-12-04 20:15:34 · answer #7 · answered by dnsnowden 2 · 1 1

fedest.com, questions and answers